PENINGKATAN USAHA OPAK PEDAS MANIS PAK SULAWI CAP ANGSA DI KAVLING LAMA SWADAYA BATUAJI KOTA BATAM - Suswanto Ismadi Megah; Sri Sugiharti; Rasyid Ridho Harahap; Calvin Avalycotesvara Arintiarno Lee (ASOSIASI IDEBAHASA KEPRI, 2026)
Small and medium enterprises managed by Mr. Sulawi are something extraordinary, because with a very minimal educational background but are able to provide jobs for many people. In this PKM activity, input is provided on how this UMKM business can grow rapidly. Home-based bread businesses that are managed by bringing the Brand Image from their hometown, namely Sweet Spicy Opak Business of Pak Sulawi’s Angsa Brand, are able to compete in big cities like Batam. With the name Sweet Spicy Opak Business of Pak Sulawi’s Angsa Brand